2009
DOI: 10.3390/ijerph6082205
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Addiction Severity Index Japanese Version (ASI-J) as a Treatment-Customization, Prediction, and Comparison Tool for Alcohol-Dependent Individuals

Abstract: Objective:To demonstrate the usefulness of the Addiction Severity Index Japanese Version (ASI-J) in Japanese alcohol-dependent individuals. The ASI is a frequently used clinical and research instrument that measures severities in seven functional domains in people with substance abuse disorders.Methods:A total of 370 male inpatients with a history of alcohol dependence participated in the study. Forty-nine participants were excluded in the final analysis due to lack of reliability (i.e., patient misrepresentat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…The reliability of our study was found to be consistent with a good Cronbach's alpha estimates for the ASI-5-BM, in keeping with data from the US, 14 Netherlands, 9 China, 5,15 Switzerland 8 and Japan. 6 Alpha values for the medical and occupation domain are lesser than 0.7. For the medical domain (0.581), this is probably due to the reporting of how many times there were hospitalized as opposed to how many days that they were in the hospital.…”
Section: Copyrightmentioning
confidence: 94%
See 2 more Smart Citations
“…The reliability of our study was found to be consistent with a good Cronbach's alpha estimates for the ASI-5-BM, in keeping with data from the US, 14 Netherlands, 9 China, 5,15 Switzerland 8 and Japan. 6 Alpha values for the medical and occupation domain are lesser than 0.7. For the medical domain (0.581), this is probably due to the reporting of how many times there were hospitalized as opposed to how many days that they were in the hospital.…”
Section: Copyrightmentioning
confidence: 94%
“…9 In Japan, the internal consistency of the ASI data was also found to be good; 0.79 for medical status; 0.67 for employment status; 0.67 for alcohol use; 0.49 for drug use; 0.76 for legal status; 0.66 for family/social relationships; and 0.71 for psychiatric status. 6 Demirbas et al, 7 in testing external reliability through test-retest correlation among 31 subjects for 10 days, found correlation values of 0.85 for medical status; 0.75 for employment status; 0.84 for legal status, 0.85 for alcohol use; 0.83 for family / social relationships and 0.91 for psychiatric status. Good correlation values (0.70 -0.92) were also obtained by Luo et al 5 of between 0.70-0.92.…”
Section: Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The information for the self-perceived mental health status was gathered before stating the guidance for overcoming drug dependence using a questionnaire based on the Addiction Severity Index—5th Edition [18,19]. The interviewer asked the participants yes/no questions, including “Have you experienced any of the following emotions within past 30 days before the arrest?” The items covered included: the experience of serious depression (associated with difficulties in daily functioning, sadness, hopelessness, or loss of interest); serious anxiety or tension (unreasonably worried or the inability to feel relaxed); hallucinations; trouble understanding, concentrating, or remembering; trouble controlling violent behavior, including episodes of rage or violence; serious thoughts of suicide (seriously considering a plan for taking their own life); and attempted suicide.…”
Section: Methodsmentioning
confidence: 99%
“…It is used to compare individuals with drug abuse across different populations [8,9]; to assess the differential effects of specific drugs on specific areas of life of individuals with drug abuse [10]; to assess domains associated with certain drug use related risks [11]; to determine the relationship between the addiction severity of proband and parental variables [12].…”
Section: Introductionmentioning
confidence: 99%